The Influence of Leg Muscle Strength On The Anticipation of Takedown Slam Techniques In Athlete Tapak Suci Brebes District (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of leg muscle strength on the ability to anticipate takedowns in martial arts athletes in Tapak Suci Brebes Regency. Upper limb muscle strength plays an important role in maintaining body stability and balance when facing a slam attack. This study used a quasi-experimental method with a one-group pretest-posttest design. The research subjects consisted of 16 active pencak silat athletes. The research instruments included a wall sit test to measure leg muscle strength and an expert-validated takedown anticipation scoring rubric. Data analysis was performed using a paired sample t-test and a simple linear regression test using SPSS. The results showed a significant increase in leg muscle strength and the ability to anticipate the takedown technique after treatment, with a significance value (p < 0.001). The regression results showed a correlation coefficient (R) of 0.638 and a coefficient of determination (R²) of 0.407, which means that 40.7% of anticipation ability is influenced by leg muscle strength. The significance value in the ANOVA test of 0.008 (